Student engagement, non-cognitive variables, and career choice of grade 12 STEM students - Lacuesta, Francheska Marie V. (College of Education, University of the Philippines Diliman, 2020)
When the Department of Education implemented the K-12 curriculum in 2013, many students chose the Science, Technology, Engineering, and Mathematics (STEM) academic strand. However, as observed by the researcher, after two years in senior high school, a number has left STEM strand for varied reasons. The current study sought to determine the (1) main reasons of students for pursuing STEM careers, (2) relationship of the different dimensions of students' engagement in the STEM strand to specific noncognitive variables, and (3) differences between Grade 12 STEM students with and without a firm decision to pursue a STEM career in terms of those different dimensions of students' engagement in the STEM strand, and non-cognitive variables. Data were gathered from 337 Grade 12 STEM students from different private educational institutions in the City of Manila who has shown firm decision to pursue STEM as well as those who have not. Using a questionnaire to measure student engagement and the other non-cognitive variables, the data were analyzed using Pearson r and multivariate analysis of variance (MANOVA). Based on the results, there are significant positive relationships within the different dimensions of student engagement, and within non-cognitive variables. Moreover, significant positive relationships also exist between dimensions of student engagement and non-cognitive variables, particularly self-efficacy, outcome expectations, and intent to persist in STEM. There is also sufficient evidence to say that there is a statistically significant difference across the levels of Grade 12 STEM students with and without firm decision to pursue STEM career choices on a linear combination in terms of different dimensions of student engagement and non-cognitive variables mediating career choice. It is, therefore, recommended that to motivate STEM students to stay on course, homeroom and career programs should tap into the students' behavioral and emotional engagement, self-efficacy, and persistence in STEM.